2003
DOI: 10.1046/j.1525-1438.2003.13007.x
|View full text |Cite
|
Sign up to set email alerts
|

Is bacterial vaginosis associated with cervical intraepithelial neoplasia?

Abstract: Previous research has produced conflicting results regarding the association of bacterial vaginosis (BV) and cervical intraepithelial neoplasia (CIN). These studies have been weakened in their conclusions mainly by failure to adequately control for the presence of sexually transmitted infections (STIs). One proposed mechanism suggesting that carcinogenic nitrosamines acting either independently or via human papilloma virus (HPV) has not been fully tested previously. We undertook a prospective, case-controlled,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
2
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 13 publications
1
20
2
3
Order By: Relevance
“…According to Boyle et al [11] women with BV were not found to have CIN more frequently than women with normal vaginal flora.…”
Section: Discussionmentioning
confidence: 95%
“…According to Boyle et al [11] women with BV were not found to have CIN more frequently than women with normal vaginal flora.…”
Section: Discussionmentioning
confidence: 95%
“…Alternatively, there might also be effect modification of association of HPV with CIN due to the presence of other RTIs. There is some evidence to suggest that bacterial vaginosis is not associated directly with CIN [18] and abnormal production of nitrosamines has been implicated [19]. However, biological associations such as synergism of other RTIs with occurrence of CIN cannot be ruled out emphatically [19].…”
Section: Introductionmentioning
confidence: 99%
“…Кроме того, доказано, что БВ повышает риск зараже-ния ВИЧ [10], Neisseria gonorrhoeae, Clamydia trachomatis, Human herpes virus. Следует отдельно отметить, что нару-шения микрофлоры влагалища считаются кофактором развития цервикальной неоплазии (CIN), что связано с определенной ролью состояния влагалищного микро-биоценоза в восприимчивости к вирусу папилломы чело-века [11][12][13][14].…”
Section: инфекцииunclassified